β-Ideals of β-Subalgebras via Cubic Intuitionistic Set: Prakasam Muralikrishna, Arsham Borumand Saeid‬, R. Vinodkumar, Govindasamy Palani - Team, Support (Thai Journal of Mathematics, 2022)
Cubic intuitionistic fuzzy sets are an effective and versatile technique for encoding ambiguous data. In this paper, the notion of β-ideals have been merged with cubic intuitionistic set. The perception of cubic intuitionistic ideals of β-algebra is established with relavent results. Moreover, various properties on Cartesian product and the homomorphism of cubic intuitionistic ideals of β-algebra are studied. Further, multiplication of cubic intuitionistic β-ideals is introduced and few of its related results were investigated.